Highly Efficient Ni-Fe Based Oxygen Evolution Catalyst Prepared by A Novel Pulse Electrochemical Approach. (1st September 2017) - Wang, Gongwei; Zheng, Dong; Liu, Dan; Harris, Joshua; Si, Jingyu; Ding, Tianyao; Qu, Deyang
Abstract: Ni-Fe based materials have attracted extensive attention as oxygen evolution reaction (OER) catalysts. Herein, we reported the fabrication of a superaerophobic Ni-Fe based OER catalyst by a novel and controllable pulse electrochemical approach. Unlike a traditional pulse electrodepositon which was done either cathodically or anodically, in our method both anodic and cathodic current are alternately adopted in a single pulse. Therefore, porous Ni-Fe nanosheets were self-assembled directly onto the Ni foil substrate owing to an in-situ dissolution/re-precipitation process and gas-releasing induced effect. The as-prepared Ni-Fe based electrode exhibits excellent catalytic activity and outstanding durability towards OER. The overpotential for the OER is as low as 250 mV at 10 mA/cm 2 . The catalytic reaction can last over 140 h without observable decay. The Tafel slope for the catalytic reaction is only 29.7 mV/dec. The high electrocatalytic performance is attributed to both the enhancement of its intrinsic activity and the self-optimizing microstructure of electrode.